2014
DOI: 10.7566/jpsj.83.024703
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional Crossover of the Fulde–Ferrell–Larkin–Ovchinnikov State in Strongly Pauli-Limited Quasi-One-Dimensional Superconductors

Abstract: The Fulde-Ferrell-Larkin-Ovchinnikov (FFLO) state is examined in quasi-one-dimensional s-wave and d-wave superconductors with particular attention paid to the effect of the Fermi-surface anisotropy. The upper critical field H c2 (T ) is found to exhibit a qualitatively different behavior depending on the ratio of the hopping energies t b /t a and the direction of the FFLO modulation vector q, where t a and t b are the intra-and interchain hopping energies, respectively. In particular, when t b /t a < ∼ 0.1 and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…As it was shown in Ref. [45], if the corrugation of the Fermi surface due to the interchain coupling is taken into account, the system looses its 1D character at T → 0 resulting in the finite value of the H c2 (T → 0). Figure 3 presents the normalized correction of T c = T c − T cP due to the orbital effect as a function of T cP /T c0 for different directions of the applied field.…”
Section: Resultsmentioning
confidence: 73%
“…As it was shown in Ref. [45], if the corrugation of the Fermi surface due to the interchain coupling is taken into account, the system looses its 1D character at T → 0 resulting in the finite value of the H c2 (T → 0). Figure 3 presents the normalized correction of T c = T c − T cP due to the orbital effect as a function of T cP /T c0 for different directions of the applied field.…”
Section: Resultsmentioning
confidence: 73%
“…4. In particular, the onset curve for H a exhibits a peculiar "S" shape, a limited behavior at around 0.8 K and an increase again below 0.3 K. The behavior for H a resembles that observed in the pressure-induced superconductivity in (TMTSF) 2 PF 6 [147], and is recently theoretically treated within the FFLO scenario [133,135]. What is more, unusual modulation in in-plane field-angle φ dependence of T onset c is observed above 3.0 T. In particular, the maxima of the T onset c (φ) curve, which is located at φ = 0 • (H a) and φ = 90 • (H b ) at low fields, the latter is found to shift away from the crystalline b axis at high fields.…”
Section: High-field Superconducting Statementioning
confidence: 68%
“…12(b). Indeed, it is theoretically shown that the FFLO state with q FFLO a generally acquires high T c in a Q1D system [135]. Observation of unusual phenomena resulting from the symmetry breaking with such a fixed q FFLO can be a hallmark of the Q1D FFLO state.…”
Section: High-field Superconducting Statementioning
confidence: 97%
“…However, in lower‐dimensional systems this detrimental effect is suppressed due to geometric constraints. [ 31,32,53 ] As a result, (quasi‐)1D systems are a good environment to search for the elusive FFLO state.…”
Section: Unconventional Pairing Phasesmentioning
confidence: 99%